Direct Surface Modification of the Epidermis Using Mussel-Inspired Polydopamine with Multiple Anti-Biofouling Functions - Lee, Su Eon; Lee, Hanna; Kim, Jang Hwan; Park, Sungwook; Oh, Young Taek; Choi, Hayoung; Kim, Jeong Min; Jo, Hye Jun; Park, Jun Hyun; Jin, Ho Jun; Lee, Kwan Hyi; Han, Seung Ho; et al. (Advanced Healthcare Materials, 2025)
The surface properties of the epidermis are crucial in pathogen adhesion and proliferation. Moreover, damage to the epidermis caused by various physical and chemical attacks provides a favorable environment for pathogen penetration and proliferation through the exposed internal living tissue. Surface modification of the epidermis to impart anti-biofouling properties can provide effective protection against infections. In this study, a facile method of imparting multiple anti-biofouling functions by directly modifying the epidermal surface of an organism using dopamine, which is a mussel-inspired substance, is introduced. Biocompatible polydopamine (PDA) is uniformly applied to organic surfaces with diverse morphological features and surface energies, indicating its versatility. In addition, the reliability of epidermal modification with PDA is confirmed via the PDA-induced prevention of chronic changes in the impedance of the epidermis. Critically, the PDA-modified epidermis exhibited various anti-biofouling functions, including antibacterial and anti-adsorption properties against bacteria and cellular/noncellular microorganisms, respectively. Improved antibacterial properties are successfully realized via integration with tobramycin, which is a representative antibiotic. Direct surface modification using PDA offers an innovative approach to safeguard biological surfaces, particularly the human epidermis, against various pathogens, with potential for application in medical patches and skin-attached devices.
Keywords: Antibacterials; Antibiofouling; Antivirals; Direct coatings; Facile method; Living tissues; Polydopamine; Polydopamine coating; Property; Surface-modification; antibacterial; antiviral; direct coating; polydopamine coatings; surface modifications